Feminizacja zawodu nauczycielskiego – „różowe kołnierzyki” i paradoksy rynku pracy - Gromkowska-Melosik, Agnieszka (Wydawnictwo Naukowe UAM, 2013)
Statistical dominance of women in the teaching profession, particularly at the level of elementary education in almost every country of the world is a fact. The author in the article tries to fi nd the reasons for low status of this profession, at present and in historical context as well as and its social consequences. The feminization of teaching profession is considered taking into account two dimensions. First is purely statistical, referring to the absolute and the percentage of women in the teaching profession. Second one regarded as a sociological phenomenon with its implication to education. There are two possible approaches to the relationship between the feminization of the teaching profession and its place in the occupational stratifi cation, expressed e.g. in prestige and income. The fi rst results from the conviction that feminization of teaching profession is a consequence of its permanently weaker position in the occupational structure. This belief dominates many theoretical analyzes and also common sense of millions people. In the fi eld of academic discussion this approach is expressed by gender segregation and desegregation theory, and the inverted hierarchy mechanism theory. However, a closer analysis of this phenomenon makes possible to support radically different interpretation of this problem. So, proponents of the second approach argue that this is not the case that feminization of the teaching profession has brought its degradation. They are convinced that weak status of this profession in occupational structure is a consequence of its feminization. Growing number of women diminishes the attractiveness of this job. At he end of article author concludes that this context, generally the growth of women within this „pink-collar profession” is either a refl ection of its historically low prestige in the structure of employment or it is connected with the reduction of its prestige because of social or economical reasons.
Feminization of Teacher’s Profession – „Pink Collars“ and Paradoxes of Labor Market
Keywords: teacher profession; feminization; gender inequality; structure of job market; pinkcollar workers